Exploration of Students' Autonomous Learning Motivation in Educational Technology Environments - Zhaoqiong W. U.; I Nyoman Jampel; I Wayan Sukra Warpala (Universitas Pendidikan Ganesha, 2025)
The main problem in student independent learning is low intrinsic motivation, which is often hampered by educational platform designs that are not sufficiently supportive. In addition, the influence of cultural factors and learning support mechanisms on the quality of independent learning is not yet fully understood. This study aims to analyze the factors that influence students' self-directed learning motivation, evaluate the role of educational technology platform design, and synthesize the relationship between motivation types and learning quality with reference to the Self-Determination Theory (SDT) framework. This study uses a mixed method with a sequential explanatory design. The quantitative subjects consisted of 400 students who used Learning Management Systems, mobile learning applications, and AI-based tutor systems, while 30 students were involved in the qualitative stage through semi-structured interviews and platform log analysis. Data were collected through SDT-based questionnaires, interview guidelines, and digital activity logs. Analysis was conducted using Pearson's correlation test, regression, and qualitative thematic analysis to reinforce the findings. The results showed that intrinsic motivation was the strongest predictor of self-directed learning quality, followed by identified regulation, while extrinsic motivation played a weaker role. The study concluded that self-directed learning motivation is driven by psychological needs, platform design, and cultural background, with intrinsic motivation as the main driver. The study's implications encourage developers, educators, and policymakers to deliver educational technology that is not only access-oriented but also effective.